PENGARUH BELANJA MODAL DAN TINGKAT INFLASI TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN / KOTA DI PROVINSI KALIMANTAN BARAT TAHUN 2009-2013 - B01112007, Nenengsih (Jurnal Pembangunan dan Pemerataan, 2016)
ABSTRACTEconomic growth is the indicator of economic development. The development of a region shows that theres an economic growth, followed by the development of budgeting, one of those is capitat budgeting. The purpose of this study was to determine and analyze the effects of capital spending and the rate of inflation toward economic growth in the district / city in the province of West Kalimantan year 2009-2013 . Data analysis techniques used in this research is multiple linear regression with random effect design , using a data processing program eviews 8. The results showed that the independent variable capital expenditure has significant positive effect on economic growth with a significant level of 0.0049 > 0.05 . the inflation rate has positive effect and not significant on the economic growth with a significant level of 0.8186 > 0.05 . Overall capital expenditure variable and the inflation rate have a significant effect on economic growth.Keywords : economic growth , capital expenditures , inflation rate